Symptomatic Hyperammonemia With Erwinia chrysanthemi–derived Asparaginase in Pediatric Leukemia Patients. Issue 4 (May 2018) - Gossai, Nathan; Richards, Michael; Boman, Lara; Messinger, Yoav; Gernbacher, Sara; Perkins, Joanna; Bostrom, Bruce
Abstract : Erwinia chrysanthemi –derived asparaginase is increasingly integral to acute lymphoblastic leukemia therapy. In our series, 16% of patients developed symptomatic hyperammonemia following Erwinia administration with symptoms including refractory nausea, vomiting, profound fatigue, malaise, and coma. This series of patients receiving Erwinia indicates higher than expected incidence of hyperammonemia, correlation between ammonia and asparaginase levels and therapeutic asparaginase activity levels despite dose reduction. The series provides evidence for investigation into which patients require intervention to prevent toxicity, which patients may have ammonia levels used as an asparaginase activity surrogate and which patients may achieve equivalent efficacy with abridged dosing. Abstract : Supplemental Digital Content is available in the text.